Low expression of insulin-like growth factor binding protein 7 associated with poor prognosis in human glioma. (June 2014) - Tian, Xiangyang; Zhang, Ling; Sun, Laiguang; Xue, Yihong; Xie, Shuang
Objectives: To investigate insulin-like growth factor binding protein 7 (IGFBP7) mRNA levels in human glioma and normal brain tissue, and to determine their clinical significance. Methods: In this retrospective study, IGFBP7 mRNA was quantified by real-time reverse transcription–polymerase chain reaction in brain tissue samples from patients with glioma and normal control subjects. Kaplan–Meier and Cox proportional hazards analyses were performed to determine any clinical and prognostic associations. Results: IGFBP7 mRNA levels were significantly lower in glioma tissue ( n  = 120) than in normal brain tissue ( n  = 20). Low (i.e. below the median, 5.9) IGFBP7 mRNA levels were significantly associated with larger tumour size (≥5 cm, compared with <5 cm, diameter). Patients with high (above median) IGFBP7 had longer overall survival than those with low IGFBP7. Tumour grade and IGFBP7 mRNA level were independent predictors of overall survival. Conclusions: IGFBP7 downregulation is associated with poor prognosis in glioma, and this molecule may represent both a prognostic marker and a potential therapeutic target.